GRAMMATICAL ERRORS IN THE TENTH GRADE STUDENTS’ NARRATIVE WRITING - Theresia Indah Noor Aini (Magister Scientiae, 2019)
The present study examined the students’ grammatical errors and source of errors in their narrative essays. This was a descriptive qualitative research method with a case study design. 84 tenth-grade students of SMA X Surabaya in the 2012-2013 school year participated in this study. The source of data of this research included 84 copies of the students’ narrative essays written in English. The data were the grammatically incorrect sentences. The instrument used for data collection of this study was a narrative writing assignment. The collected data were then analyzed to discover the error types, their frequency of occurrence, and then their sources. The results showed that the grammatical errors which the students made in their personal narrative essays included errors in (a) verb form or tense, (b) shift in tense, (c) plurality of nouns, (d) articles, (e) adjectives or adverbs, (f) prepositions, (g) sentence construction, (h) subject-verb agreement (i) possessive pronoun and contraction, (j) sentence coordination, (k) fused sentence, and (l) pronoun reference. The sources of the above-mentioned grammatical errors included (a) interference from the students’ native language, (b) intra-lingual and developmental factors, (c) communication strategies, and (d) context of learning. The errors caused by interference from the students’ L1 included errors in phonology/orthography, morphology, grammar, lexico-semantic and style. The errors were also attributed by inter-lingual or developmental factors, such as overgeneralization, ignorance of rule restrictions, false analogy, hyperextension, hypercorrection, and faulty categorization. The communication strategies causing the errors included paraphrasing, substitution, words coinage, and language switch. The last source was context of learning which was caused by the teacher, teaching materials, or the order of presentation. The errors show that actually the students still have problems on grammar. Therefore, the students should learn more and the teachers should develop more material and teaching technique. And the teachers should also stress the comparison between Bahasa Indonesia as their first language and English as their second language.